The Melting Curve of Nickel Up to 100 GPa Explored by XAS. Issue 12 (26th December 2017) - Boccato, Silvia; Torchio, Raffaella; Kantor, Innokenty; Morard, Guillaume; Anzellini, Simone; Giampaoli, Ruggero; Briggs, Richard; Smareglia, Alessandro; Irifune, Tetsuo; Pascarelli, Sakura
Abstract: Precise knowledge of the melting temperatures of iron, nickel, and their alloys at pressures of the deep Earth would allow us to better constrain the parameters used for the Earth's heat budget and dynamics. However, melting curves of transition metals at pressures approaching 100 GPa and above are still controversial. To address this issue, we report new data on the melting temperature of nickel in a laser‐heated diamond anvil cell up to 100 GPa obtained by X‐ray absorption spectroscopy (XAS), a technique rarely used at such conditions. We couple this for the first time to ex situ analysis of the sample, providing a further validation of the melting criterion adopted here. Finally, a Simon‐Glatzel fit to the melting data obtained in this work, combined with those obtained in the most recent X‐ray diffraction experiments, gives T M ( K ) = 1727 × P M 17 ± 3 + 1 1 2 . 5 ± 0 . 1, defining the most up‐to‐date X‐ray‐determined melting curve for Ni. This result confirms that Ni could be ignored in the discussion on melting properties and thermal profile of the Earth's core, as it should affect the Fe melting point by only 10–20 K at 90 GPa. Key Points: The melting curve of nickel was determined for the first time using X‐ray absorption (XAS) and validated by post analysis up to 100 GPa The X‐ray‐determined P ‐ T phase diagram of nickel is extended by providing the minimum melting temperature for Ni up to 100 GPa A Simon‐Glatzel fit describes the most recent X‐ray‐determined melting curve: the melting point at the ICB is not affected by Ni